Comparative evaluation of antimicrobial efficacy of triple antibiotic paste and amoxicillin clavulanate paste as an intracanal medicament against Enterococcus faecalis: An in vitro study - Dhandayuthapani Sasikala; Parisa Norouzi Baghkomeh; Jamaluddin Mohammed Farzan (Wolters Kluwer Medknow Publications, 2024)
Background: Triple antibiotic paste (TAP) is the commonly used intracanal medicament against Enterococcus faecalis. Amoxicillin clavulanate paste (ACP) is recommended as a "fall-back" antibiotic when traditional dental antibiotics fail. Literature comparing the antimicrobial efficacy of TAP and ACP in eradicating E. faecalis from the root canal system is sparse; hence, this in vitro study was conducted to evaluate and compare the antimicrobial efficacy of TAP and ACP as an intracanal medicament for endodontic treatment of single-rooted permanent teeth against E. faecalis. Materials and Methods: This in vitro, experimental study evaluated 60 root samples obtained from extracted single-rooted human permanent teeth. The canal diameter was enlarged and subsequently infected with E. faecalis for 21 days. Four groups of the contaminated samples were treated with TAP, ACP, calcium hydroxide (positive control), and saline (negative control), respectively. Dentinal shavings were collected at the end of the 1st, 7th, and 10th day and inoculated in agar plates. The number of colony-forming units was determined, and the data were statistically analyzed using the Kolmogorov-Smirnov and Shapiro-Wilks test. P <0.05 was considered statistically significant. Results: The mean number of E. faecalis colony counts across all 3 test days demonstrated that TAP exhibited the highest inhibition of bacterial growth, followed by ACP which is not statistically significant (P = 1.00). Conclusion: Considering the limitations of this in vitro study, the findings suggest that ACP could be an effective alternative intracanal medicament to TAP for endodontic therapy.